The notion of that which depends on us in Plotinus and its background - Eliasson, Erik. (Philosophia Antiqua, 2008)
The book analyses Plotinus' notion of 'that which depends on us', which although central to his ethics, has never been examined in a specific study before. The book traces the sources of this notion in Aristotle and its reception in Stoicism, Middle Platonism and Early Aristotelian Commentators. It then shows how Plotinus' critical discussion of the inherent problems in previous accounts and his investigation of the notion's application to the Intellect and the One, leads to a highly original interpretation of the notion as central to his account of human agency. The book demonstrates Plotinus' serious engagement with the central issues of ancient ethics, and his original way of tackling them.